HUBUNGAN PENGETAHUAN DENGAN TINGKAT KECEMASAN SISWA PUTRI SEKOLAH DASAR DALAM MENGHADAPI MENARCHE TAHUN 2023 - Tamba, Roslita Maria; Maulani, Rici Gusti; Purba, Netty Herawaty (LPPM Institut Pendidikan Nusantara Global, 2023)
A maximum In indonesian society, menstrual problems are still considered taboo to talk about, so early adolescents lack good enough knowledge and attitudes about the physical and psychological changes related to menarche. The purpose of this research was to determine the relationship between knowledge and the level of anxiety of elementary school female students in facing menarche in 2023. This research used analytical methods with a cross-sectional approach. The population in this study was 133 students of V and VI grades in Public Elementary School 009 Botania Batam. Purposive Sampling Process used Slovin Technique. Data collection by observation and questionnaire distribution. This statistical test using Chi-square parametric test. The results of the univariate analysis of the majority of respondents' knowledge were sufficient with 33 students (57.9%) and the majority of respondents' anxiety level facing menarche was at the level of not anxious with 34 students (59.6%). The results of the bivariate analysis showed a significant relationship between the knowledge of female students and the level of anxiety in dealing with menarche. (p.value 0.001). It is expected that the educational institution will take preventive action by conducting education about premarital sexual behavior in students